Beneficial effects of Saccharomyces boulardii CNCM I-745 on clinical disorders associated with intestinal barrier disruption - Terciolo C; Dapoigny M; Andre F (Clinical and Experimental Gastroenterology, 2019)
Chloe Terciolo,1,2 Michel Dapoigny,3 Frederic Andre4 1INRA, UMR 1331 Toxalim, Research Center in Food Toxicology, F-31027 Toulouse, France; 2Aix-Marseille Université, INSERM, UMR 911, CRO2, Marseille, France; 3Médecine Digestive, CHU Estaing, CHU Clermont-Ferrand, Université Clermont Auvergne, INSERM UMR 1107, Neuro-Dol, Clermont-Ferrand, France; 4Centre de Recherche en Cancérologie de Marseille (CRCM), INSERM U1068, CNRS UMR 7258, Aix-Marseille Université and Institut Paoli-Calmettes, Parc scientifique et technologique de Luminy, Marseille, France Abstract: Intestinal barrier defects lead to “leaky gut syndrome”, defined as an increase in intestinal permeability that allows the passage of luminal content into intestinal tissue and the bloodstream. Such a compromised intestinal barrier is the main factor underlying the pathogenesis of inflammatory bowel disease, but also commonly occurs in various systemic diseases such as viral infections and metabolic syndrome. The non-pathogenic yeast Saccharomyces boulardii CNCM I-745 has demonstrated its effectiveness as a probiotic in the prevention and treatment of antibiotic-associated, infectious and functional diarrhea. Via multiple mechanisms of action implicated in intestinal barrier function, S. boulardii has beneficial effects on altered intestinal microbiota and epithelial barrier defects in different pathologies. The well-studied probiotic yeast S. boulardii plays a crucial role in the preservation and/or restoration of intestinal barrier function in multiple disorders. This could be of major interest in diseases characterized by alterations in intestinal barrier function. Keywords: Saccharomyces boulardii CNCM I-745, apical junctional complex, leaky gut syndrome, intestinal barrier function, intestinal permeability, tight junctions